High-performance carbon nanotube electronic ratchets. Issue 10 (2nd September 2021) - Hao, Ji; Nanayakkara, Sanjini U.; Tervo, Eric J.; Blackburn, Jeffrey L.; Ferguson, Andrew J.
Abstract : High performance electronic ratchet devices capable of harvesting energy from periodic, stochastic, and even noisy electronic voltage signals are enabled by semiconducting carbon nanotube networks with asymmetric dopant/counterion distributions. Abstract : The rapid advancements in low-power portable/wearable electronic devices require concurrent development of technologies that can provide power without the need for bulky, heavy battery storage. Electronic ratchets, asymmetric transistor-based devices that can convert AC signals or electronic noise into DC power, have been proposed as one solution to this growing need. The recent demonstration of conjugated polymer-based electronic ratchets offers a route toward lightweight, flexible power sources for portable applications. Here we demonstrate the fabrication of the first electronic ratchets where the active channel component consists of semiconducting single-walled carbon nanotubes (s-SWCNTs), which can transform electronic noise or AC signals to a stable DC current with higher output power (up to ca. 14 mW for a chemically doped device) than their polymer-based analogs. We also show that patterning of the dopant profile in the s-SWCNT channel enables reasonable power conversion performance ( ca. 3.5 mW) with improved stability relative to homogeneously doped devices. Our findings demonstrate the promise for s-SWCNT electronic ratchets as energy harvesting devices for portable, low-power applications.